KUALITAS SEMEN BEKU SAPI SIMMENTAL TERHADAP LAMA THAWING YANG DIGUNAKAN DALAM PROGRAM INSEMINASI BUATAN DI KABUPATEN WONOSOBO TAHUN 2020 - Kurniawan, Andika Vicky; Iskandar, Faruq; Zulfanita, Zulfanita (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this reserch is to determine the effect of thawing timeon mootility, living percentage of spermatozoa, abnormalities ofspermatozoa, colour and pH of Simmental cattle frozen semen usingwater with temperature 26 oC in Wonosobo regency where the dailyaverage temperature is around 14.3 - 26.5 oC. Cattle breeding takesan important role in increasing the nasional cattle population. TheEffort to improve the Artifical Insemination (AI) technique is the keyof this goals. This research used 25 ministraw (0,25) frozen semen ofcattle Simmental from bulls in BIB Lembang. The method of thisresearch is an exsperimental method with a Completely RandomizedDesign (CRD) with a pattern of 1 x 6, A is the cattle nation namelythe Simmental cattle, B is the leght of thawing time in temperature of26 oC are T1 (5 seconds), T2 (15 seconds), T3 (30 seconds), T4 (60secons), T5(90 second), and T6 (120 second), and the treatments arerepeated 4 times each. In the order to determine the effect betweentreatments, the Duncan Multiple Range Test (DMRT) is used as thecontinue test. Based on the results, it is concluded that the thawingtechnique with different durations has an effect on motility,abnormality and survival rate of frozen semen of Simmental cattle,while the color and pH are not effected. Therefore, the resultsrevealed that the best treatment is found in the T3 treatment in 30seconds as the time of thawing.